Sound and meaning of megalithic traditional village as a touristic consumption - Francisca Titing Koerniawaty; I Wayan Ardika (Institut Pariwisata dan Bisnis Internasional, 2021)
This study aims were to criticize and analyse the patterns of the cultural heritage of megalithic traditional village-Bena. The sound and meaning were to reflect the domestic and international tourists towards the cultural heritage of megalithic traditional village-Bena as a touristic consumption. Bena is the oldest and well-preserved of a megalithic traditional village located in Ngada Regency, East Nusa Tenggara Province. This qualitative study with ethnographic approach led to depth analysis on tourists’ perception towards the megalithic traditional village of Bena as a touristic consumption. The minority of tourists’ complaint constructs or damages, doesn’t it?